Leadership in Action : Issues and Observations - The Narrative Lens and Organizational Change - Graham, Stedman (Center for Creative Leadership, 2009)
The business world in recent years has shown increasing interest in the narrative lens and more specifically in the relationship between leadership storytelling and organizational change.